Advanced Energy‐Storage Architectures Composed of Spinel Lithium Metal Oxide Nanocrystal on Carbon Textiles. Issue 11 (5th July 2013) - Shen, Laifa; Ding, Bing; Nie, Ping; Cao, Guozhong; Zhang, Xiaogang
Abstract Current battery technologies are known to suffer from kinetic problems associated with the solid‐state diffusion of Li+ in intercalation electrodes materials. Not only the use of nanostructure materials but also the design of electrode architectures can lead to more advanced properties. Here, advanced electrode architectures consisting of carbon textiles conformally covered by Li4Ti5O12 nanocrystal are rationally designed and synthesized for lithium ion batteries. The efficient two‐step synthesis involves the growth of ultrathin TiO2 nanosheets on carbon textiles, and subsequent conversion into spinel Li4Ti5O12 through chemical lithiation. Importantly, this novel approach is simple and general, and it is used to successfully produce LiMn2O4/carbon composites textiles, one of the leading cathode materials for lithium ion batteries. The resulting 3D textile electrode, with various advantages including the direct electronic pathway to current collector, the easy access of electrolyte ions, the reduced Li+/e− diffusion length, delivers excellent rate capability and good cyclic stability over the Li‐ion batteries of conventional configurations.